Gestión ambiental de residuos sólidos urbanos municipales en la ciudad de Tumbes abril a diciembre, 2 004 - Niquen Inga, Vicente Lorenzo (2012)
The purpose of the present work of investigation was to analyse the system of collection of urban solid wastes that the Provincial City Hall of Tumbes at present executes to propose a system of Ambiental Management in the collection of the solid wastes of the city. Previously, it was determinated the characteristics of the urban solid wastes; per capita production, physics composition, density and moisture analyzing 167 samples taken by means of stratified random sampled with optimum afixation and distributed in three social-economical strates: NA = 49; NM = 72; NB = 46, from three elected zones by means of simple random sampled. Of the same way, it was analysed the number and turns of the collecting units, modality and total quantity of collected solid wastes, percentage of covering of service, necessary number of units for the collection, routes, type of ambiental management that the Provincial City Hall of Tumbes executes and the level of knowledge of the citizenship about ambiental education during the period from January to july 2 004. It was determined that the total quantity of solid wastes that is collected in the city of Tumbes is 42,00 m/day with a mean per capita production of 0,31 kg/h/day; moisture 70,09 % and density of 221,28 kg/m3; being the greater component, the organic matter with 59,36%. Of the same way, the covering of collection is 80,95% with a deficit in the service of 19,05% giving the appearance of “throwing places” in informal surroundings places of the city, it is what originates the pollution of the environment, the routes of collection are not correctly planned and it only obeys to a historical be haviour. The collectivity shows a lacking about the knowledge of ambiental and sanitary education. At observing that the Provincial City Hall of Tumbes has not foreseen at short time any plan of ambiental management of solid wastes, it is planned as a proposal a Program of Ambiental Management based on the ambiental rules ISO – 14 000, that gets better the present system of collection of urban solid wastes generated in the city of Tumbes and that it contributes to lessen the grade of the existence ambiental pollution.